2018
DOI: 10.1007/s00125-017-4542-6
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6-mediated transcriptional suppression of Txnip is critical for pancreatic beta cell function and survival in mice

Abstract: Sequence data have been deposited in the National Institutes of Health (NIH) Gene Expression Omnibus (GEO) with the accession code GSE104161.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 43 publications
1
41
0
Order By: Relevance
“…Conversely, Sirt6 overexpression protects against palmitate-induced β-cell dysfunction and apoptosis (Song et al, 2016 ; Xiong et al, 2016 ). Recently, a new study found that Sirt6 is critical for pancreatic β-cell function and survival in mice (Qin et al, 2018 ). Sirt6 deficiency does not affect endocrine morphology, β-cell mass or insulin production but did result in glucose intolerance and defective glucose-stimulated insulin secretion in mice (Qin et al, 2018 ).…”
Section: Sirt6 and Glucose Metabolismmentioning
confidence: 99%
See 3 more Smart Citations
“…Conversely, Sirt6 overexpression protects against palmitate-induced β-cell dysfunction and apoptosis (Song et al, 2016 ; Xiong et al, 2016 ). Recently, a new study found that Sirt6 is critical for pancreatic β-cell function and survival in mice (Qin et al, 2018 ). Sirt6 deficiency does not affect endocrine morphology, β-cell mass or insulin production but did result in glucose intolerance and defective glucose-stimulated insulin secretion in mice (Qin et al, 2018 ).…”
Section: Sirt6 and Glucose Metabolismmentioning
confidence: 99%
“…Recently, a new study found that Sirt6 is critical for pancreatic β-cell function and survival in mice (Qin et al, 2018 ). Sirt6 deficiency does not affect endocrine morphology, β-cell mass or insulin production but did result in glucose intolerance and defective glucose-stimulated insulin secretion in mice (Qin et al, 2018 ). β-cell specific deletion of Sirt6 reproduced the defect in insulin secretion.…”
Section: Sirt6 and Glucose Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…β-cells of pancreas showed decreased sensitivity when Sirt6 is inhibited. Sirt6 deficiency increases H3K9Ac, H3K56Ac levels and active RNA polymerase II at the promoter region of Txnip, causing expression of Txnip that promotes β-cell apoptosis [47].…”
Section: Sirt6mentioning
confidence: 99%